JOGJA ECO2 CITIES: KONSEP TATA KOTA UNTUK MEWUJUDKAN YOGYAKARTA SEBAGAI KOTA ECOLOGIES DAN ECONOMICS MELALUI INTEGRASI TRANSPORTASI MASAL - Wibowo, Achmad Kunaryo; Nur Utari, Khoirunisa Ulya; Sarifudin, Rochmat (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Civil growth level in Jogjakarta regency appearently brings a positive impact on the economic growth level. Economic growth level in a certain area also always give negative impact, like a public stagnation and air polution. To recovering that problem, it needs a city rearrangement planning that can maximize the economic potential in each distric in Jogjakarta and also to minimize the negative impact. This study tries to make a new concept to replanning the city arrangement design that has an ecological and economic value. Literature review shows transportation design through the integrated public transportation will connect every economic sector in every Regency in Jogjakarta. The public transportation to study include trolley bus, commuter line, and aerobuswhich has a specific row that separated from the private transportation. The transportation design inside the main city will provide the row for the bicycle or the unmottorized vehicle and the pedestrian. It can reduce the air polution from the motorized vehicle. The regency design with a social housing principle can be build from the money raised by the goverment. To maximize the system, it may also try to integrate the solar energy to fulfill the necessary of the public. The regency planning âshared placeâ with the circuit breaker of the vehicle and the road design will also provide a âshared placeâ, jogging and sport track, and also the community amusement for public.Keywords: economic potential, social housing, transportation design.